ANALISIS PENGARUH CASH RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON EQUITY PADA PT. KALBE FARMA TBK PERIODE TAHUN 2014 – 2018 - Ependi Ependi; Ali Putra Alamsyah (JURNAL LENTERA AKUNTANSI, 2020)
The author takes the title Analysis of the Effect of Cash Ratio and Debt to Equity Ratio Against Return on Equity at PT. Kalbe Farma Tbk Period 2014 - 2018 to find out how much influence the Cash Ratio and Debt to Equity Ratio on Return on Equity contained in PT. Kalbe Farma Tbk during the period 2014 - 2018. In this study the existing variables are independent variables namely Cash Ratio and Return on Equity. While the dependent variable is Return on Equity. This research is a quantitative study in which the object in this study is PT. Kalbe Farma Tbk within the period 2014 - 2018. With this method, research data is compiled, interpreted, described and analyzed. Through the measurement of financial ratios which are widely used as a method of financial statement analysis, this study will use ratio analysis as a method of analysis. The research data were processed by statistical analysis with the classic assumption test and hypothesis test. The financial ratios used are liquidity ratios, solvency ratios, and profitability ratios. The results showed that partially and simultaneously Cash Ratio and Debt to Equity Ratio had no effect on Return on Equity. R Square value of 0.941. This means that Cash Ratio and Debt to Equity Ratio have an influence on Return on Equity of 94.1% while the remaining 5.9% is influenced by other variables that are not in the linear regression model. Keyword: Analysis of the Effect of Cash Ratio and Debt to Equity Ratio Against Return on Equity